Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, S.; Nijmeijer, E.; Bragonzoni, L.; Dingshoff, E.; Gokeler, A.; Benjaminse, A. (European Journal of Sport Science, 2023)
Modifiable (biomechanical and neuromuscular) anterior cruciate ligament (ACL) injury risk factors have been identified in laboratory settings. These risk factors were subsequently used in ACL injury prevention measures. Due to the lack of ecological validity, the use of on-field data in the ACL injury risk screening is increasingly advocated. Though, the kinematic differences between laboratory and on-field settings have never been investigated. The aim of the present study was to investigate the lower-limb kinematics of female footballers during agility movements performed both in laboratory and football field environments. Twenty-eight healthy young female talented football (soccer) players (14.9 ± 0.9 years) participated. Lower-limb joint kinematics was collected through wearable inertial sensors (Xsens Link) in three conditions: (1) laboratory setting during unanticipated sidestep cutting at 40-50°; on the football pitch (2) football-specific exercises (F-EX) and (3) football games (F-GAME). A hierarchical two-level random effect model in Statistical Parametric Mapping was used to compare joint kinematics among the conditions. Waveform consistency was investigated through Pearson`s correlation coefficient and standardized z-score vector. In-lab kinematics differed from the on-field ones, while the latter were similar in overall shape and peaks. Lower sagittal plane range of motion, greater ankle eversion, and pelvic rotation were found for on-field kinematics (p < 0.044). The largest differences were found during landing and weight acceptance. The biomechanical differences between lab and field settings suggest the application of context-related adaptations in female footballers and have implications in ACL injury prevention strategies.